2018
DOI: 10.19045/bspab.2018.700159
|View full text |Cite
|
Sign up to set email alerts
|

Residual effect of biochar and summer legumes on soil physical properties and wheat growth

Abstract: Biochar, a carbon-rich solid material and legumes having numerous benefits to the soil-plant system gaining a keen interest as an innovative sustainable approach among the agriculture research community in many parts of the world especially in developing countries in order to enhance soil quality and ensure food security. Thus, with the same approach, we have carried out a field experiment to examine the residual effect of biochar application and summer legumes on soil physical properties and subsequent wheat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The previously published research articles from this work reported that residual biochar, coupled with summer legumes significantly enhanced the fertility of the soil in terms of specific macro (N, P, K) and micronutrients (Cu, Fe, Zn, and Mn), soil physical properties such as water-holding capacity, saturation percentage, reduced bulk density of soil and improved the growth of the wheat crop such as plant height, the number of grains per spike, spikes m -2 , and spike length. Keeping the advantages of all these previously published results in consideration, it is evident that aged biochar, coupled with summer legumes, significantly enhanced the yield of wheat crop (Rahim et al, 2019;Rahim et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The previously published research articles from this work reported that residual biochar, coupled with summer legumes significantly enhanced the fertility of the soil in terms of specific macro (N, P, K) and micronutrients (Cu, Fe, Zn, and Mn), soil physical properties such as water-holding capacity, saturation percentage, reduced bulk density of soil and improved the growth of the wheat crop such as plant height, the number of grains per spike, spikes m -2 , and spike length. Keeping the advantages of all these previously published results in consideration, it is evident that aged biochar, coupled with summer legumes, significantly enhanced the yield of wheat crop (Rahim et al, 2019;Rahim et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…The detailed information about materials and methods can be found in our recently published articles (Rahim et al, 2019;Rahim, Mian, Arif, Ahmad, & Khan, 2020). Briefly, Field-scale experiment for enhancing wheat yield with the aged effect of biochar and summer legumes were carried out on farmland located at the University of Agriculture Peshawar-Pakistan.…”
Section: Methodsmentioning
confidence: 99%
“…Ali et al (2015) published that biochar significantly increased yield of wheat and soil fertility in two years study under wheat-maize-wheat cropping system. Comparably, Rahim et al (2019) published that biochar and legumes have pleasant effect on the physical properties of soil.…”
Section: Discussionmentioning
confidence: 99%
“…Organic amendments have been shown to improve soil chemical and physical properties and increase yield of crops (e.g. Atkinson et al 2010;Gomez 2013;Rahim et al 2019).…”
Section: Water Holding Capacitymentioning
confidence: 99%